Higher Daily Physical Activities Continue to Preserve Muscle Strength After Mid-Life, But Not Muscle Mass After Age of 75. Issue 22 (May 2016) - Hwang, An-chun; Zhan, Yu-Rui; Lee, Wei-Ju; Peng, Li-Ning; Chen, Liang-Yu; Lin, Ming-Hsien; Liu, Li-Kuo; Chen, Liang-Kung
Abstract : Abstract: The objective of this study is to explore the impact of aging and daily physical activities (PA) on muscle mass and muscle strength among community-dwelling people in Taiwan. The design is a cross-sectional study. Setting is a population-based community study. One thousand eight hundred thirty-nine community-dwelling people aged 50 years and older in Taiwan participated in the study. Measurements include demographic characteristics, Charlson Comorbidity Index (CCI) for multimorbidity, mini-nutritional assessment (MNA) for nutritional evaluation, functional autonomy measurement system (SMAF) for functional capacity, Chinese version mini mental state examination (MMSE), 5-item Taiwan Geriatric Depression Scale (TGDS-5), Chinese version of International Physical Activity Questionnaire (IPAQ), height-adjusted skeletal muscle index (SMI) by dual-energy X-ray absorptiometry, handgrip strength, timed 6-m walking test for usual gait speed. Laboratory measurements include testosterone, sex-hormone binding globulin (SHBG), dehydroepiandrosterone sulfate (DHEA-S), insulin-like growth factor-1 (IGF-1), high-sensitivity C-reactive protein (hsCRP), 25-OH vitamin D, and insulin resistance. After adjusted for age, the lowest PA tertile was associated with multimorbidity, poorer functional capacity and nutritional status, more depressive symptoms, lower SMI and lower handgrip strength, and lower free androgen index (FAI) in men. The negative association between PA and low SMI was more significant among subjects aged younger than 65 and the association decreased with older age. For subjects aged younger than 65, moderate daily PA (Q2) group had lower risk of low SMI compared with Q1 participants (OR: 0.62, 95% CI = 0.39–0.98, P = 0.040). For muscle strength, higher daily PA was associated with lower risk of low handgrip strength after age of 65 and the effect was dose-dependent. The effect was attenuated by potential confounders during age 65 to 74, while after age 75, the result was almost unchanged in fully adjusted model (OR = 0.37, 95% CI = 0.18–0.79, P = 0.010). Older age may attenuate the protective effects of higher daily PA on preventing muscle loss, but higher daily PA continues to preserve muscle strength at different age groups, even after the age of 75. The prognostic role of daily PA may be mediated by muscle strength instead of muscle mass among people aged 75 years and older.